THE ROLE OF PERCEIVED RELIGIOUS SIMILARITY IN THE QUALITY OF MOTHER-CHILD RELATIONS IN LATER-LIFE: DIFFERENCES WITHIN FAMILIES AND BETWEEN RACES - Sechrist, Jori (2011)
Despite evidence of the importance of value similarity in predicting parent-adult child relations, little attention has been given to the unique role of religious similarity. Using 1,407 dyads nested within 390 families, we examine whether religious similarity predicts the quality of mother-child relations in later life, and whether the strength of this association differs by race. Consistent with our hypotheses, religious similarity was found to be an important factor in predicting both closeness and conflict, particularly in Black families. These findings suggest that it may be important to give greater attention to religion when studying patterns of interaction and support in the later years, especially among Black families.